La tecnologia MagDrive di Trimble S6 - Lemmon, T.; Jung, R.; Santarsiero, Domenico (GEOmedia, 2008)
Trimble S6 MagDrive Technology Trimble MagDrive Technology is based on an electromagnetic frictionless direct drive concept, similar to those used in the locomotive industry. Applying this solution to entire stations represents a major improvement in the numeric control approach for instruments of this class.